Individual differences in cocaine-induced conditioned place preference in male rats: Behavioral and transcriptomic evidence. (October 2022) - Atehortua Martinez, Luisa Alessandra; Curis, Emmanuel; Mekdad, Nawel; Larrieu, Claire; Courtin, Cindie; Jourdren, Laurent; Blugeon, Corinne; Laplanche, Jean-Louis; Megarbane, Bruno; Marie-Claire, Cynthia; Benturquia, Nadia
Background: Substance use disorder emerges in a small proportion of drug users and has the characteristics of a chronic relapsing pathology. Aims: Our study aimed to demonstrate and characterize the variability in the expression of the rewarding effects of cocaine in the conditioned place preference (CPP) paradigm. Methods: A cocaine-CPP paradigm in male Sprague–Dawley rats with an extinction period of 12 days and reinstatement was conducted. A statistical model was developed to distinguish rats expressing or not a cocaine-induced place preference. Results: Two groups of rats were identified: rats that did express rewarding effects (CPP expression (CPPE), score >102 s) and rats that did not (no CPP expression (nCPPE), score between −85 and 59 s). These two groups did not show significant differences in a battery of behavioral tests. To identify differentially expressed genes in the CPPE and nCPPE groups, a whole-transcriptome ribonucleic acid-sequencing analysis was performed in the nucleus accumbens (NAc) 24 h after the CPP test. Four immediate early genes ( Fos, Egr2, Nr4a1, and Zbtb37 ) were differentially expressed in the NAc of CPPE rats after expression of CPP. Variability in cocaine-induced place preference persisted in the CPPE and nCPPE groups after the extinction and reinstatement phases. Transcriptomic differences observed after reinstatement were distinct from those observed immediately after expression of CPP. Conclusion: These new findings provide insights into the identification of mechanisms underlying interindividual variability in the response to cocaine's rewarding effects.